Research on the braking force model of brake discs based on thermal stress distribution - JIANG Fangyu; GAO Qiang; YAN Pengfei; ZAN Xiaolei; LI Yaning (Jixie chuandong)
ObjectiveTo precisely calculate the brake disc braking force of a disc brake system, a brake disc braking force model based on the quasi-static temperature and thermal stress distribution of the brake pad under the influence of heat source was established.MethodsFirst, the energy conversion mechanism during a single braking process was analyzed. Then, based on the quasi-static temperature and thermal stress distribution obtained during the braking process, a stress-braking force model was constructed using numerical methods. Finally, a simulation example was designed to verify the validity of the model.ResultsThe simulation results show that, in the later stages of braking, the temperature-braking force model curve is observed to be slightly higher than the stress-braking force model due to the influence of thermal accumulation effects. The stress-braking force model and the temperature-braking force model exhibit a high degree of consistency in their trends, with a maximum error of 305 N, an average error of 2.371 5 N, and the average relative error of only 0.012 7%. This model not only provides a basis for the numerical analysis of the braking force, but also provides new ideas and methods for the braking force detection.